The Relationship between Parenting and Adolescent Character Values - Mullis, Zhona Ratu; Mudjiran, Mudjiran (Current Issues in Counseling, 2023)
This research is motivated by the phenomenon of studentsThe type of research used is quantitative with a correlational descriptive approach. The research subjects used were students of SMP Negeri 22 Kerinci with a total population of 223 students. The research sample was taken using a sampling techniqueproportional random samplingas many as 144 students. The type of data used is interval data. In collecting data using parenting relationship instruments with adolescent character values with a Likert scale model. The research findings show that parents' parenting varies in general in a fairly good category with a percentage of 72.2%, while character values are in a good category with a percentage of 61.1%. The results of the correlation analysis found a positive and significant relationship between parenting and adolescent character values with an rcount of 0.2203 with a significant level of 0.0080.